Mortality of Hemato-Oncologic Patients Admitted to a Pediatric Intensive Care Unit: A Single-Center Experience - Pechlaner, Agnes; Kropshofer, Gabriele; Crazzolara, Roman; Hetzer, Benjamin; Pechlaner, Raimund; Cortina, Gerard (Frontiers in Pediatrics, 2022)
Introduction Mortality of children with hemato-oncologic disease admitted to a paediatric intensive care unit (PICU) is higher when compared to the general population. The reasons for this remain unexplored. The aim of this study was to assess outcomes and trends of hemato-oncologic patients admitted to a paediatric intensive care unit (PICU), with analytical emphasis on emergency admissions. Methods Patients with an hemato-oncologic diagnosis admitted to a tertiary care university hospital PICU between 1st January 2009 and 31st December 2019 were retrospectively analysed. Additionally, patient mortality six months after PICU admission and follow-up mortality until 31st December 2020 were recorded. Measurements and Main Results: We reviewed a total of 701 PICU admissions of 338 children with hemato-oncologic disease, of which 28.5% were emergency admissions with 200 admissions of 122 patients. Of these, 22 patients died, representing a patient mortality of 18.0% and an admission mortality of 11.0% in this group. Follow-up patient mortality was 25.4% in emergency-admitted children. Multivariable analysis revealed severe neutropenia at admission and invasive mechanical ventilation as independent risk factors for PICU death (p=0.029 and p=0.002). The total number of PICU admissions of hemato-oncologic patients rose notably over time, from 44 in 2009 to 125 in 2019. Conclusion: Although a high proportion of emergency PICU admissions of hemato-oncologic patients required intensive organ support, mortality seemed to be lower than previously reported. Moreover, in this study, total PICU admissions of respective children rose notably over time.